Swedish Archaeology in the Twenty-First Century - The Necessity of a (self-) Critical Dialogue - Karlsson, Håkan (Current Swedish Archaeology, 2000)
In this paper it is argued that the rapid changes that have taken place within Swedish archaeology during the last decades can be discussed under the headings of structural, economical, public and theoretical changes and problems. It is also stressed that, taken together, these problems constitute a serious "crisis" in contemporary Swedish archaeology. So far, discussions seem to have focused mainly on the structural problems, while the economical, public and theoretical problems have been more or less neglected. Therefore, the aim of this paper is to il discuss the structural, economical, public and theoretical changes that have taken place in Swedish archaeology during the last decades and point to both the problems and the possibilities created by them, and ii) discuss the present structural, economical and public problems from a theoretical perspective by stressing that these problems can, at least partly, be solved within the framework of an awareness of the (self-) critical possibilities inherent in some of the theoretical reasoning of the last decades.